PENGARUH PROMOSI PENJUALAN DAN LOKASI TERHADAP KEPUTUSAN PEMBELIAN DI UD. BINTANG BANGGLE - Dicky Ardina Putra; Nuruni Ika Kusuma Wardhani (Eqien - Jurnal Ekonomi dan Bisnis, 2022)
The success achieved by a trading business in running a business is related to the proliferation of purchasing decisions in the store, the trading business needs to pay attention to sales promotions and location so that purchasing decisions continue to grow rapidly. In research conducted at UD. Bintang Banggle aims to determine the influence of sales promotions and locations on purchasing decisions in UD. Bintang Banggle. This research is a quantitative research using questionnaires as a method of data collection. With a population of all consumers who make purchases in UD. Bintang Banggle, this study has a sample of 60 respondents by setting Accidental sampling technique. Primary data is the data used and Partial Least Square (PLS) is the analysis tool. The results show that (1) Sales promotion has a positive and significant effect on purchasing decisions in UD. Bintang Banggle. (2) Location has a positive and significant effect on purchasing decisions in UD. Bintang Banggle.